Pengaruh Ukuran Perusahaan, Capital Intensity Dan Inventory Intensity Terhadap Agresivitas Pajak Pada Perusahaan Sektor Healthcare - Natasha; Nayla Nurul Putri; Nuraini Azlin; An Suci Azzahra (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to evaluate the impact of company size, capital intensity, and inventory intensity on tax aggressiveness behaviour in companies in the healthcare sector listed on the Indonesia Stock Exchange. The phenomenon of tax aggressiveness is an important thing to pay attention to because it can affect the clarity of financial statements and the efficiency of the tax system. This study uses a quantitative method with the use of multiple linear regression analysis, where data is taken from the company's financial statements from 2021-2024. The population was 34 companies. The sample was taken using a purposive sampling approach with a sample of 11 companies that met the requirements, because there was abnormal data, 13 data were excluded, thus obtaining a total of 42 observation data. The results of partial testing show that the three independent variables, namely company size, capital intensity, and inventory intensity, on tax aggressiveness, do not have a significant effect on tax aggressiveness. In addition, the results of simultaneous testing show that the three variables collectively have no significant effect on tax aggressiveness. This finding indicates that there are other factors outside the model that are more influential on corporate tax aggressiveness in the healthcare sector.